Inhibition of Brain GTP Cyclohydrolase I Attenuates 3-Nitropropionic Acid-Induced Striatal Toxicity: Involvement of Mas Receptor/PI3k/Akt/CREB/ BDNF Axis - Mustafa, Aya M.; Rabie, Mostafa A.; Zaki, Hala F.; Shaheen, Aya M. (Frontiers in Pharmacology, 2021)
GTP cyclohydrolase I (GTPCH I) is the rate limiting enzyme for tetrahydrobiopterin (BH4) biosynthesis; the latter is an essential factor for iNOS activation that contributes neuronal loss in Huntington’s disease (HD). The aim of the study was to investigate the neuroprotective effect of 2, 4-diamino-6-hydroxypyrimidine (DAHP), GTPCH I enzyme inhibitor, against neuronal loss in 3-nitropropinic acid (3-NP) induced HD in rats and to reveal the possible involved mechanisms mediated through PI3K/Akt axis and its correlation to Mas receptor (MasR). Rats received 3-NP (10 mg/kg/day; i.p.) with or without administration of DAHP (0.5 g/kg/day; i.p.) or wortmannin (WM), a PI3K inhibitor, (15 μg/kg/day; i.v.) for 14 days. DAHP improved cognitive, memory and motor abnormalities induced by 3-NP, as confirmed by striatal histopathological specimens and immunohistochemical examination of GFAP. Moreover, DAHP treatment inhibited GTPCH I activity, resulting in decreased BH4 levels and iNOS activation. Also, DAHP upregulated the protein expression of survival protein; p85/p55 (pY458/199)-PI3K and pS473-Akt that in turn boosted the activation of striatal neurotrophic factors and receptor; pS133-CREB, BDNF and pY515-TrKB, which positively affect MasR protein expression and improve mitochondrial dysfunction, as indicated by enhancing both SDH and PGC-1α level. Indeed, DAHP attenuates oxidative stress by increasing SOD activity and Nrf2 expression in addition to reducing neuro-inflammatory status by inhibiting NF-κB p65 and TNF-α expression. Interestingly, all the previous effects were blocked by co-administration of WM with DAHP. In conclusion, DAHP exerts neuroprotective effect against neuronal loss induced by 3-NP administration via inhibition of GTPCH I and iNOS activity and activation of MasR/PI3K/Akt/CREB/BDNF/TrKB axis besides, its antioxidant and anti-inflammatory effect.